2015
DOI: 10.1016/j.pepi.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Rotating convective turbulence in Earth and planetary cores

Abstract: a b s t r a c tAn accurate description of turbulent core convection is necessary in order to build robust models of planetary core processes. Towards this end, we focus here on the physics of rapidly rotating convection. In particular, we present a closely coupled suite of advanced asymptotically-reduced theoretical models, efficient Cartesian direct numerical simulations (DNS) and laboratory experiments. Good convergence is demonstrated between these three approaches, showing that a comprehensive understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
150
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(155 citation statements)
references
References 122 publications
5
150
0
Order By: Relevance
“…DNS investigations [60] and laboratory experiments [1,14] show excellent agreement with the simulations of the QG convection equations. In particular, Stellmach et al [60] showed that it is necessary to reach very small Ekman numbers (Ek 10 −7 ) and Rossby numbers (Ro 0.05) to reach the asymptotic regime in which the dipolar structure of the inversecascade-generated vortex is preferred over the cyclonic vortices that become predominant in the broken-symmetry regime present at higher Ekman and Rossby numbers [24,27,53,66].…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…DNS investigations [60] and laboratory experiments [1,14] show excellent agreement with the simulations of the QG convection equations. In particular, Stellmach et al [60] showed that it is necessary to reach very small Ekman numbers (Ek 10 −7 ) and Rossby numbers (Ro 0.05) to reach the asymptotic regime in which the dipolar structure of the inversecascade-generated vortex is preferred over the cyclonic vortices that become predominant in the broken-symmetry regime present at higher Ekman and Rossby numbers [24,27,53,66].…”
Section: Introductionsupporting
confidence: 58%
“…Investigations in spherical geometries are of obvious importance for planets, but must employ lower efficiency numerics typically and are therefore more restricted in parameter space [1]. The DNS investigation of Stellmach and Hansen [59] confirmed the predictions of Soward [55] that a strong, time-oscillatory mean magnetic field can be generated near the onset of convection.…”
Section: Introductionmentioning
confidence: 70%
“…Similarly, such structures are approximately four orders of magnitude below the limits of planetary magnetic field observations. Thus, individual Λ o = 0 onset-scale convection columns, should they exist in Earth's core, are then not relevant to our interpretation of geomagnetic flux patches or their temporal variations [24,51,52].…”
Section: A Foray Into Linear Theorymentioning
confidence: 98%
“…They present numerical simulations (of rotating, Boussinesq convection in Cartesian domains) that bolster this view. Aurnou et al (2015) summarize a variety of theoretical and laboratory work on the related topic of rapidly rotating convection in Earth and planetary cores; see also King et al (2012), Stellmach et al (2014), and Cheng et al (2015) for analysis of the flow morphology and heat transport in various regimes. Separately, Julien et al (2012) have conducted simulations of asymptotically reduced equations applicable to the rapidly rotating Rayleigh-Bénard problem, and find that while heat transport in the weakly-rotating limit is essentially set by the properties of the boundary layers, transport in the rapidly rotating regime is set by properties in the bulk.…”
Section: Basics Of Convection and Rotationmentioning
confidence: 99%